2021
DOI: 10.2147/jir.s309008
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms in Genes Involved in the Type I Interferon System (IFIH1/MDA-5, TNFAIP3/A20, and STAT4): Association with SLE Risk in Egyptian Children and Adolescents

Abstract: Purpose: Systemic lupus erythematosus (SLE) is a multifactorial autoimmune inflammatory disease that is influenced by both genetic and environmental factors and associated with dysregulation of type I interferon (INF) response. This study aimed to investigate the effects of single nucleotide polymorphisms (SNPs) of the IFIH1, TNFAIP3, and STAT4 genes in the type I INF system on SLE risk in Egyptian children and adolescents. Patients and Methods: We recruited 94 SLE individuals and 94 healthy subjects. SNPs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
2
1
Order By: Relevance
“…Although IFIH1, RSAD2, and PARP9 were found to be associated with a variety of autoimmune or inflammatory disease development, such as SLE, RA, Sjögren’s syndrome (SS), type 1 diabetes (T1D), and AITD ( Frommer and Kahaly, 2021 ; Zedan et al, 2021 ), we did not find that these genes were differentially expressed between the recurrent GD group and the normal group. Ubiquitin-specific peptidase 18 (USP18) plays a crucial role in the development of Th17 cells and can regulate the differentiation and function of Treg cells ( Yang et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 68%
“…Although IFIH1, RSAD2, and PARP9 were found to be associated with a variety of autoimmune or inflammatory disease development, such as SLE, RA, Sjögren’s syndrome (SS), type 1 diabetes (T1D), and AITD ( Frommer and Kahaly, 2021 ; Zedan et al, 2021 ), we did not find that these genes were differentially expressed between the recurrent GD group and the normal group. Ubiquitin-specific peptidase 18 (USP18) plays a crucial role in the development of Th17 cells and can regulate the differentiation and function of Treg cells ( Yang et al, 2021 ).…”
Section: Discussioncontrasting
confidence: 68%
“…Genome wide association studies in SLE patients has demonstrated single nucleotide polymorphisms (SNPs) in loci near IFN related genes, in particular interferon regulatory factor 5 (IRF5), IRF7, IRF8, STAT4 and Tyk2, that are associated with the risk of developing SLE in adults ( Sigurdsson et al, 2005 ; Graham et al, 2007 ). Consistent with these observations, using a candidate gene approach of type I IFN related genes, the T allele of rs3747517 in the IFIH1 gene was associated with a reduced risk of SLE while the T allele of rs7574865 in STAT4 was associated with an increased risk of developing SLE in children and adolescents ( Zedan et al, 2021 ). In conjunction with our understanding of type I IFN in mouse models with SLE and translational studies demonstrating increased expression of type I IFN and related pathways in SLE, these genetic studies strongly support an important role for type I IFN related pathways in SLE pathogenesis and the potential for translation of these findings to the care of patients with SLE.…”
Section: Biology and Function Of Type I Interferonsmentioning
confidence: 62%
“…3 Among Egyptian patients, different genetic polymorphisms have been studied and found to be associated with SLE as polymorphisms in the gene coding for the autoimmune regulator (AIRE), type I interferon (IFN) pathway, interleukin 27, programmed cell death 1 (PD1), tumor necrosis factor (TNF-α) and IFN-γ. [4][5][6][7][8] However, the role of the human leukocyte antigen-G (HLA-G) gene has not been addressed before among Egyptian patients.…”
Section: Introductionmentioning
confidence: 99%